Handbook of solid waste management - Kreith, Frank (McGraw-Hill, 1994)
The solution to the mounting problems in the management of municipal solid wastes lies in the application of a variety of minimization and disposal techniques. This practical handbook offers engineers and public officials an integrated approach to the planning, design and management of efficient, environmentally-responsible solid waste disposal systems. Over 20 experts from industry and government provide all the tools needed to design cost-effective systems using such diverse methods as waste reduction, recycling and reuse, composting, incineration and landfilling. The work also take an in-depth look at current environmental legislation, including 1990 amendments to the Clean Air Act and RCRA subtitle D regulations, and outlines proven procedures for dealing with the policy and social issues surrounding facilities siting and programme financing.